PENGARUH SARANA PRASARANA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT NUR HIDAYAH BANTUL YOGYAKARTA - Totok Sundoro; Parmadi Sigit Purnomo; Gina Maratus solihah (Jurnal Solusi, 2022)
The obligation of the hospital is to provide correct information about hospital services to the community, to provide safe, quality, anti-discriminatory, and effective health services by prioritizing the interests of patients in accordance with hospital service standards. The quality of services expected by patients who use hospital services related to the quality of hospital services is still largely limited, both in terms of personnel, facilities and infrastructure, availability of drugs, facilities, costs and medical services. Preliminary studies in this research are informed that there are still customer complaints related to facilities and equipment, as well as services in inpatient rooms. This research is a quantitative descriptive study with a cross sectional approach. To measure infrastructure and service quality on patient satisfaction, the multiple linear regression method was used with 80 respondents. The results of the research that has been done that the variables in this study consisting of infrastructure and service quality have a significant influence on patient satisfaction